Pengaruh Location, Electronic Word Of Mouth dan Social Media Marketing terhadap Purchase Interest Property Sharia Islamic Soreang PT. Sharia Green Land Nagrak - Ridwan Maulana; Dedy Ansari Harahap; Moch. Malik Akbar Rohandi (Bandung Conference Series: Business and Management, 2023)
Abstract. This study aims to determine the application of Location, Electronic Word of Mouth and Social Media Marketing carried out by Sharia Islamic Soreang Nagrag PT Sharia Greenland, to find out the responses of respondents regarding Location, Electronic Word of Mouth and Social Media Marketing carried out, to find out the responses of respondents regarding Interests Buy, to find out the influence of Location, Electronic Word of Mouth and Social Media Marketing on Buying Interests Sharia Islamic Soreang Property PT. Sharia Green Land Nagrak. This research is a type of descriptive and verification research using quantitative research methods. The data collection technique used in this study was by distributing questionnaires. The sampling technique in this study is using simple random sampling ach. The population in this study is someone who has purchased products from Sharia Islamic Soreang and obtained a sample of 140 respondents. Analysis of the data used in this study is using analysis, statistical t test and F statistical test. The results of this study state that location partially has a significant effect on purchase intention, electronic word of mouth partially has a significant effect on purchase intention, social media marketing has a significant effect on purchase intention, and location, electronic word of mouth and social media marketing simultaneously have a significant effect. on Buying Interest variable. Abstrak. Penelitian ini bertujuan untuk mengetahui penerapan Location, Electronic Word of Mouth dan Social Media Marketing yang dilakukan Sharia Islamic Soreang Nagrag PT Sharia Greenland, untuk mengetahui tanggapan responden mengenai Location, Electronic Word of Mouth dan Social Media Marketing yang dilakukan, untuk mengetahui tanggapan responden mengenai Purchase Interest, untuk mengetahui besar pengaruh Location, Electronic Word of Mouth dan Social Media Marketing terhadap Purchase Interest Property Sharia Islamic Soreang PT. Sharia Green Land Nagrak. Penelitian ini merupakan jenis penelitian deskriptif dan verifikatif dengan menggunakan metode penelitian kuantitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu dengan menyebar kuesioner. Teknik sampling dalam penelitian ini yaitu menggunakan teknik simple random sampling. Populasi dalam penelitian ini merupakan seseorang yang mengunjungi kantor pemasaran Sharia Islamic Soreang dan didapatkan sampel 140 orang responden. Analisis data yang digunakan dalam penelitian ini yaitu menggunakan analisis, uji statistik t dan uji statistik F. Hasil penelitian ini menyatakan bahwa Location secara parsial berpengaruh signifikan terhadap Purchase Interest, Electronic Word of Mouth secara parsial berpengaruh signifikan terhadap Purchase Interest, Social Media Marketing berpengaruh signifikan terhadap Purchase Interest, dan Location, Electronic Word of Mouth dan Social Media Marketing secara simultan berpengaruh signifikan pada variabel Purchase Interest.